Outbreaks in Turkey Past to Present - Ketrez, Gamze; Şirin, Hülya; Hasde, Metin (Turkey Health Literacy Journal, 2020)
An epidemic is the presence of a diseases cases more than the expected rate in a particular region or community. In the present, the COVID-19 disease taught the term of epidemic to the whole world by spreading through globe. Due to this epidemic, other epidemics in history have been wondered, and a study was required in which information on the effects and struggles of our country during other epidemics was compiled from a public health perspective. It is thought that learning the history of epidemics will make a significant contribution to us in terms of how we should fight the epidemics we have experienced and those we will experience in the future. From past to the present, many epidemics have been seen all over the world. These epidemics have caused a significant number of deaths in our country as well as all over the world and caused great destructions. According to the sources, it was seen that important names in history were also affected by the epidemics. Our country has struggled to cope with these epidemics like the other parts of the world. This study aimed to examine the epidemics in our country, the control of epidemics and the measures taken in our country including some major epidemics affecting the world and our country. It has been seen that each epidemic has had great effects on our country, but the measures taken remained the same as the measures taken today in combating the epidemic. Although vaccines are found for some diseases, hand hygiene, mask and social distance still owns special importance among the measures taken and they will probably be the most important protection methods for future outbreaks too.
Keywords: Outbreak; Outbreak Control; Prevention Methods; Quarantine; Covıd-19